DNA damage induced by bare and loaded microporous coordination polymers from their ground and electronic excited states1. Issue 19 (21st May 2015) - Yañuk, Juan G.; Alomar, María L.; Gonzalez, M. Micaela; Simon, Francisco; Erra-Balsells, Rosa; Rafti, Matías; Cabrerizo, Franco M.
<x xml:space="preserve">Abstract</x> The type and extent of DNA damage depends on chemical identity of linker and metal ion center of the MCP considered. Moreover, some MCPs can provide a suitable platform for its use in photodynamic therapy.